Aortic stiffness independently predicts exercise capacity in hypertrophic cardiomyopathy: a multimodality imaging study. Issue 16 (21st July 2010) - Austin, Bethany A; Popovic, Zoran B; Kwon, Deborah H; Thamilarasan, Maran; Boonyasirinant, Thananya; Flamm, Scott D; Lever, Harry M; Desai, Milind Y
Abstract : Background: Exercise capacity in patients with hypertrophic cardiomyopathy (HCM) varies despite similar diastolic dysfunction, left ventricular outflow tract (LVOT) obstruction and mitral regurgitation (MR). Pulse wave velocity (PWV), determined by cardiac magnetic resonance (CMR), measures aortic stiffness and is abnormal in patients with HCM in comparison with controls. Objective: To determine potential clinical and imaging predictors of peak oxygen consumption (pVO2 ) in patients with HCM. Methods: Fifty newly referred patients with HCM (62% men, 44±13 years, 90% receiving optimal drugs, 18% hypertensive) underwent Doppler echocardiography (transthoracic echocardiography (TTE)), cardiopulmonary exercise testing and CMR for symptom evaluation. TTE variables (diastology, post exercise MR and LVOT gradient (mmHg)), pVO2 (ml/kg/min) and CMR variables (PWV (aortic path length between mid- and descending aorta/time delay between arrival of the foot of the pulse wave between two points, m/s), and LV volumetric indices) were measured. Results: After exercise LVOT gradient, MR, deceleration time and pVO2 were 104±52, 1±1, 240±79 ms, and 25±6, respectively. Mean basal septal thickness (cm), PWV, EF, ESV index (ml/m 2 ), EDV index (ml/m 2 ) and LV mass index (g/m 2 ) were 1.9±0.5, 9.3±7, 64%±7, 32±9, 87±17 and 112+36, respectively. Multiple regression analyses showed that only age (β=−0.38, p=0.004) and PWV (β=−0.33, p=0.01) predicted pVO2 . Conclusion: In patients with HCM, age and PWV are predictors of pVO2, independent of LV thickness, LVOT gradient and diastolic indices. Aortic stiffness potentially has a role in evaluation of symptoms of patients with HCM.